IMPLEMENTASI MEDIA BERBASIS TEKNOLOGI INFORMASI SEBAGAI MEDIA PEMBELAJARAN OLEH GURU BIOLOGI DI SMA NEGERI SE-KABUPATEN DELI SERDANG - DIAN PERAYANTI SINAGA (JURNAL ILMIAH SIMANTEK, 2019)
This study aims to 1) To describe the availability of IT-based learning media in Deli Serdang District High School, 2) To describe the use of IT-based learning media in Deli Serdang District High School, 3) To describe the application of Information Technology-based media by Biology teachers in class XI of the State Servants of Deli Serdang District, and 4) To describe the problems and obstacles experienced by Biology teachers in the application of Information Technology-Based Media in class XI of Deli Serdang District High School. This study uses a type of quantitative research with descriptive methods. the population is all Se-regency district biology teachers. The subjects in this study were biology teachers in class XI. From the results of the questionnaire regarding the completeness of IT-based learning media for Tanjung Morawa 1 High School, Percut Seituan 1 Public High School, and 1 Pancur Batu Public High School obtained a percentage of 55.56% and for Namorambe 1 Public High School, Bangun Purba 1 Public High School and Public High School 1 Galagng obtained a percentage of 44.44%. From the results of the questionnaire regarding the condition of IT-based learning media for Namorambe 1 Public High School amounting to 11.11%, for State High School 1 Percut Sei Tuan, Galan 1 High School and Panacur Batu 1 High School at 55.56%, for Tanjung Morawa 1 Public High School and Bangun Purba 1 Public High School at 33.33%. The average score of the utilization of TI-based learning media in the Deliserdang District High School is 55.81. The application of media in the process of biology learning at Deliserdang District High School was 48% in the form of powerpoint. Factors that influence the use of media include: 1) Availability and condition of the media, 2) availability of internet networks, 3) teachers lack mastery and understanding in operating IT-based media. The teacher is easier to use media that is already available in schools such as pictures and torso